Benefit of ultra-high-density mapping-guided radiofrequency reablation in pulmonary vein isolation non-responders after initial cryoballoon procedure. Issue 6 (3rd May 2020) - Straube, Florian; Dorwarth, Uwe; Hartl, Stefan; Brueck, Benedikt; Pongratz, Janis; Kosmalla, Alexander; Wankerl, Michael; Hoffmann, Ellen
Abstract: Aims: Symptomatic atrial arrhythmias despite complete pulmonary vein isolation (PVI) are common. The purpose was to evaluate ultra-high-density multi-electrode electroanatomical mapping-guided radiofrequency ablation (RFA) in PVI non-responders. Methods and results: Ultra-high-density multi-electrode electroanatomical mapping-guided RFA in consecutive symptomatic atrial fibrillation (AF) patients after initial cryoballoon PVI was performed. Patients were included if all pulmonary veins (PVs) were still isolated. Radiofrequency targets were atrial tachycardia (AT), extra-PV trigger, and/or substrate. Procedural results and outcome were evaluated. Of 95 patients, 67 (70.5%) with complete PVI were included (70 years, CHA2 DS2 Vasc 2.9, left atrium 45 mm, persistent AF 45%, AT 45%). The median time to reablation was 26 months. One hundred and seven maps (1.6/patient) and 11.890 ± 9.018 electrograms were acquired in 33 ± 12 min. Twenty-eight percent of the left atrial (LA) wall showed pathological voltage signals, predominantly at the anterior (37%) and septal wall (26%). Atrial tachycardia (49 left, 4 right) were ablated in 35 patients (52%), extra-PV trigger in two patients (3%). One atrioventricular nodal re-entry tachycardia and seven right atrial isthmus ablation (10%) were performed. In 32 patients (48%), no AT was present and substrate-based ablation was performed. Mean LA area ablated was 7 ± 6 cm 2 (7%). No major complication occurred. The mean follow-up time was 772 ± 317 days. Freedom from atrial arrhythmia recurrence off antiarrhythmic drugs was 49% at 12 months. Conclusion: Pulmonary vein isolation non-responders are older, mainly suffering from complex atrial arrhythmias. Left atrial substrate is predominantly located at the anterior and septal wall. Ultra-high-density multi-electrode electroanatomical mapping-guided RFA is safe and effective. At 1 year, 5 out of 10 patients were in stable sinus rhythm off antiarrhythmic drugs.